An Examination of Educational Leadership Preparation in Ontario: Are Principals Prepared to Lead Equitably? - Spooner, Nia (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2024)
In response to the changing demographics of schools in Canada and efforts to better equip principals to challenging inequity, leadership preparation programs have adopted new policies focused more on leading with an equity lens. However, studies have demonstrated a disconnect between what is covered in these leadership programs and how school principals actually perceive their ability to lead equitably and work with diverse learners. Six current school principals and vice principals in Ontario, Canada who have successfully completed a Principal Qualification Program (PQP) course were interviewed to understand their perceptions on the program’s ability to prepare them to lead, and their perceptions on concepts of equity, diversity, and inclusion (EDI). The racial experiences and identities of each participant shaped their definitions of EDI, as well as their understandings of difference. Study findings indicate several critical areas of change for principal preparation programs in Ontario: training guidelines, efforts to prepare educators to be equitable leaders, and the educators’ perceptions on their preparedness to lead. Utilization of Critical Race Theory in Education and Applied Critical Leadership additionally help frame analysis and support the need to integrate culturally relevant pedagogical practice into leadership preparation programs.